Passagens da ditadura à democracia: a reconstrução do Estado de Direito no Brasil e na República Tcheca - Souza, Alexandre Nogueira (Universidade Federal de São Carlos, 2025)
This study sought to analyze the political transition that occurred in Brazil and Czechoslovakia, with an emphasis on rebuilding the Rule of Law after the reconquer of democratic system in these countries. By demonstrating the importance of the Constitution and Rule of Law for the development of the State and the citizen throughout history, it became possible to advance the debate exposing the Brazilian Military Dictatorship (1964-1985) and the Socialist Regime of Czechoslovakia (1948-1989). Furthermore, the passages from dictatorship to democracy in Brazil and Czechoslovakia are developed. Finally, a reflection was made regarding the restructuring of the Rule of Law and the guarantee of democratic institutions in the chosen countries, considering the phases of transition, consolidation and improvement of democracy. The main idea of this scientific research is to comprehend whether the way in which the transition was carried out reflected in the stability of the institutions of the Rule of Law and the validity of democratic regimes in the mentioned places. As a result, it can be affirmed that both countries, through the promulgation of a Constitution, facilitated the reestablishment of the Rule of Law and Democracy. The difference lies in the transition model. Brazil was marked by a verticalized process of slow, gradual, and secure nature, which resulted in greater difficulties in the reinstitution of democracy. In contrast, the Czech Republic, by breaking with socialist foundations through horizontality and a peaceful revolution, found it easier to restore the democratic regime.
Passages from dictatorship to democracy: the reconstruction of the Rule of Law in Brazil and the Czech Republic
Keywords: Instituições políticas; Transição política; Estado de Direito; Constituição; Democracia; Political institutions; Political transition; Rule of Law; Constitution; Democracy; CIENCIAS HUMANAS::CIENCIA POLITICA::ESTADO E GOVERNO